2017
DOI: 10.1002/dta.2250
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an optical biosensor for rapid monitoring of adalimumab in serum of patients with Crohn's disease

Abstract: Therapeutic drug monitoring of adalimumab is recommended to improve therapeutic outcome in patients with Crohn's disease. Performing an ELISA requires a rather long time-to-result and the necessity of collecting multiple samples to decrease the cost per adalimumab determination. In this study, we aim to develop and validate a rapid assay suitable for measuring a single adalimumab serum sample using a fiber-optic surface plasmon resonance (FO-SPR) based sensor. Therefore, we have immobilized MA-ADM28B8 as captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Bian et al, have reported a study evaluating adalimumab in Crohn’s disease patients’ serum by fibre optic SPR (FO-SPR). Anti-TNF-α mAb was immobilised using self-assembling monolayer (SAM) having high detection sensitivity [ 72 , 73 ]. However, (comparing our study to that reported by Bian) we used direct immobilisation which has been widely used in studies involving proteins [ 17 , 74 ], thereby avoiding the SAM formation step and taking advantage of the chip for functionalising it and directly evaluating anti-TNF-α antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Bian et al, have reported a study evaluating adalimumab in Crohn’s disease patients’ serum by fibre optic SPR (FO-SPR). Anti-TNF-α mAb was immobilised using self-assembling monolayer (SAM) having high detection sensitivity [ 72 , 73 ]. However, (comparing our study to that reported by Bian) we used direct immobilisation which has been widely used in studies involving proteins [ 17 , 74 ], thereby avoiding the SAM formation step and taking advantage of the chip for functionalising it and directly evaluating anti-TNF-α antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…For functionalization, we adopted the method we proposed before with minor modifications [22]. Biofunctionalization was performed through a four-step process: carboxylic group functionalization with 11-mercaptoundecanoic acid; carboxylic group activation using a 0.4 M EDC/0.1 M NHS mixture solution; antibody immobilization; blocking.…”
Section: Surface Functionalizationmentioning
confidence: 99%
“…Sufficient signal amplification is required when developing BLI into a biosensor. Gold nanoparticles proved to be an effective enhancer in surface plasmon resonance-based optical biosensors ( Bian et al, 2018 ; Lu et al, 2016 ), but their enhancing effect in BLI-based optical biosensors seems limited, as reflected by a recent study wherein maximal signals of approximately 3 nm were obtained for semi-quantitative detection of SARS-CoV-2 BAbs ( Dzimianski et al, 2020 ). Meanwhile, 3,3′-diaminobenzidine tetrahydrochloride (DAB), a metal precipitating substrate, combined with secondary antibody-conjugated horseradish peroxidase (HRP), is a more effective strategy for improving BLI signals ( Auer et al, 2015 ; Gandolfini et al, 2017 ; Gao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%